Endothelial Dysfunction is Associated With Increased Incidence, Worsened Severity, and Prolonged Duration of Acute Kidney Injury After Severe Trauma. Issue 3 (March 2021) - Hatton, Gabrielle E.; Isbell, Kayla D.; Henriksen, Hanne H.; Stensballe, Jakob; Brummerstedt, Martin; Johansson, Pär I.; Kao, Lillian S.; Wade, Charles E.
ABSTRACT: Introduction: Nearly half of severely injured patients suffer acute kidney injury (AKI), but little is known about its pathogenesis or optimal management. We hypothesized that endothelial dysfunction, evidenced by elevated systemic soluble thrombomodulin (sTM) and syndecan-1, would be associated with higher incidence, worsened severity, and prolonged duration of AKI after severe trauma. Methods: A single-center cohort study of severely injured patients surviving ≥24 h from 2012 to 2016 was performed. Arrival plasma sTM and syndecan-1 were measured by ELISA. Outcomes included 7-day AKI incidence, stage, and prolonged AKI ≥2 days. The Kidney Disease Improving Global Outcomes guidelines were used for AKI diagnosis and staging. Univariate and multivariable analyses were performed. Results: Of 477 patients, 78% were male. Patients had a median age of 38 (interquartile ranges [IQR] 27–54) and injury severity score of 17 (IQR 10–26). AKI developed in 51% of patients. Those with AKI were older and displayed worse arrival physiology. Patients with AKI had higher plasma levels of syndecan-1 (median 34.9 ng/mL vs. 20.1 ng/mL) and sTM (6.5 ng/mL vs. 4.8 ng/mL). After adjustment, sTM and syndecan-1 were both associated with higher AKI incidence, worse AKI severity, and prolonged AKI duration. The strength and precision of the association of sTM and these outcomes were greater than those for syndecan-1. A sensitivity analysis excluding patients with AKI on arrival demonstrated the same relationship. Conclusions: Elevated sTM and syndecan-1, indicating endothelial dysfunction, were associated with higher incidence, worsened severity, and prolonged duration of AKI after severe trauma. Treatments that stabilize the endothelium hold promise for AKI treatment in severely injured patients. Abstract : Supplemental Digital Content is available in the text